Pre-conditioning with the soluble guanylate cyclase activator Cinaciguat reduces ischaemia-reperfusion injury after cardiopulmonary bypass - Radovits, Tamás; Korkmaz-İçöz, Sevil; Miesel-Gröschel, Christiane; Seidel, Beatrice; Stasch, Johannes-Peter; Merkely, Béla; Karck, Matthias; Szabó, Gábor (European journal of cardio-thoracic surgery, 2011)
Objective: Activation of the nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate (NO-sGC-cGMP) pathway can induce potent cardioprotection-like effects against ischaemia-reperfusion injury and nitro-oxidative stress. We investigated the effects of pharmacological pre-conditioning with Cinaciguat (BAY 58-2667), a novel sGC activator on peroxynitrite-induced endothelial dysfunction in vitro, as well as on myocardial and coronary vascular function during reperfusion in a canine model of cardioplegic arrest and extracorporeal circulation. Methods: Isolated coronary arterial rings exposed to peroxynitrite were investigated for vasomotor function. Vehicle- and Cinaciguat-pre-treated (8.33 μg h−1 or 25 μg h−1 intravenous (IV) for 30 min) anaesthetised dogs (n = 6-7 per group) underwent hypothermic cardiopulmonary bypass with 60 min of hypothermic cardioplegic arrest. Left- and right-ventricular end-systolic pressure-volume relationship (ESPVR) was measured by a pressure-volume conductance catheter at baseline and after 60 min of reperfusion. Coronary blood flow, vasodilatation to acetylcholine and myocardial level of adenosine triphosphate were determined. Results: Pre-incubation of coronary rings with Cinaciguat improved peroxynitrite-induced endothelial dysfunction. Compared with control, pharmacological pre-conditioning with Cinaciguat (25 μg h−1) led to higher myocardial adenosine triphosphate content, to a better recovery of left- and right-ventricular contractility (Δ slope of left ventricular ESPVR given as percent of baseline: 102.4 ± 19.1% vs 56.0 ± 7.1%) and to a higher coronary blood flow (49.6 ± 3.5 ml min−1 vs 28.0 ± 3.9 ml min−1). Endothelium-dependent vasodilatation to acetylcholine was improved in the treatment groups. Conclusions: Pre-conditioning with Cinaciguat improves myocardial and endothelial function after cardiopulmonary bypass with hypothermic cardiac arrest. The observed protective effects imply that pharmacological sGC activation could be a novel therapeutic option in the protection against ischaemia-reperfusion injury in cardiac surgery.